Reflections and experiences of the Training, Update and Dissemination Program of the School of Geography, University of Costa Rica in the 2015-2021 period - Reyes-Chaves, Jonnathan (2023)
Teaching extensions are one of the functions of the Vicerrectoría de Acción Social at the Universidad de Costa Rica. Through this modality an academic exchange between teachers. and communities is offered to improve the welfare of society through the transfer of knowledge in an agile and direct way. These activities are beneficial for communities and contribute to the country's social and economic development. The Training, Update and Dissemination Program of the School of Geography (PROCADI) was created to promote geographical trade through teaching extension, attending non-formal educational needs aimed at companies, institutions, career graduates, university students, professionals and technicians from various competencies. Through a systematization of data associated with the PROCADI that are administered from the Academic and Budget Information Management System of the Vicerrectoría de Acción Social (BITE) in the 2015-2021 period it was determined that the PROCADI issues annually on average between 10 and 15 activities such as: courses, conferences, forums, seminars, among others that correspond to the themes of geomatic, society and population, environment, teaching and research, ordering and territorial planning. In general, the development of geomatic activities in the last 7 years predominate in quantity and frequencies. Traditionally, the PROCADI and the School of Geography have developed their in-person training in different spaces such as in the field, in laboratories, in auditoriums and in classrooms. However, the Covid-19 pandemic required a methodological change towards virtuality with the support of digital platforms. Among the challenges for the PROCADI, it is identified the ability to offer greater opportunities in training in the fields of territorial ordering and planning, environment, society and population, in addition to consulting and articulating the professional demands of the target audiences, as well as internationalization.